Daily Profit Analysis In Profit Management For Street Vendors In Pringapus Village, Pringapus District, Semarang District - Widya Kurnia; Enik Rahaya; Septa Intiar (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study aims to determine the daily profit management of street vendors in Pringapus Village, Pringapus District, Semarang Regency and to find out the obstacles faced in analyzing daily earnings in profit management for street vendors in Pringapus Village, Pringapus District, Semarang Regency.The research method used in this study is a qualitative research method by conducting interviews, observations and literature studies.The results obtained in this study are the average profit earned by street vendors in Pringapus village is 155 thousand. Then the street vendors in Pringapus village manage their profits by using them as daily necessities and most street vendors in Pringapus village have not mastered how to analyze profits properly and correctly due to education and age factors